FORMULASI SEDIAAN SABUN CAIR EKSTRAK ETANOL DAUN TURI (Sesbania grandiflora L.) DAN UJI ANTIJAMUR TERHADAP Candida albicans - Ering, Mariando N.; Yamlean, Paulina V. Y.; Antasionasti, Irma (PHARMACON, 2020)
ABSTRACTThe leaves of Hummingbird (Sesbania grandiflora L.) contain flavonoid compounds, saponins and tannins that are antifungal. This research aims to formulate liquid soap extracts of Hummingbird leaf ethanol and test the effectiveness of the antifungal preparations of the liquid soap of Hummingbird leaf ethanol with a concentration of 4%, 6%, 8%, 10% and 12% of the fungus growth of Candida albicans. This research uses experimental methods. The formulation of this liquid soap of Hummingbird leaf ethanol is conducted organoleptic test, pH, high foam, moisture content, free alkaline content, and type weights. Testing the effectiveness of antifungal to Candida albicans growth is done by diffusion method. Liquid soap preparations of Hummingbird leaf ethanol extract meet the standards set by SNI for organoleptic testing, pH test, Foam High test, water content test, free alkali rate test, and type weight test. Based on the anti-fungal testing of the preparation of a liquid soap extract of Hummingbird leaf ethanol to the fungus Candida albicans obtained the results of all preparations have a resistance to fungi and strong categorized.Keywords:Â  Hummingbird leaves, Liquid soap, AntifungalABSTRAK Daun Turi (Sesbania grandiflora L.) memiliki kandungan senyawa flavonoid, saponin dan tannin yang bersifat sebagai antijamur. Penelitian ini bertujuan untuk memformulasikan sabun cair ekstrak etanol daun Turi dan menguji efektivitas antijamur sediaan sabun cair ekstrak etanol daun Turi dengan konsentrasi 4%, 6%, 8%, 10% dan 12% terhadap pertumbuhan jamur Candida albicans. Penelitian ini menggunakan metode eksperimental. Formulasi sediaan sabun cair ekstrak etanol daun Turi ini dilakukan pengujian organoleptik, pH, tinggi busa, kadar air, kadar alkali bebas, dan bobot jenis. Pengujian efektivitas antijamur terhadap pertumbuhan Candida albicans dilakukan dengan metode difusi. Sediaan sabun cair ekstrak etanol daun turi memenuhi standar yang ditetapkan SNI pada pengujian organoleptik, uji pH, uji tinggi busa, uji kadar air, uji kadar alkali bebas, dan uji bobot jenis. Berdasarkan pengujian antijamur sediaan sabun cair ekstrak etanol daun Turi terhadap jamur Candida albicans didapatkan hasil semua sediaan memiliki daya hambat terhadap jamur dan dikategorikan kuat.Kata Kunci: Daun Turi, Sabun Cair, Antijamur